Konsep Peran dan Pentingnya Organisasi Relawan Teknologi Informasi dan Komunikasi (TIK) Terhadap Dimensi Sosial, Ekonomi, Lingkungan, Kesehatan dan Pendidikan - Fattah, Anwar; Wagimin, Wagimin; Hasan, Syahril (Journal of Digital Literacy and Volunteering, 2024)
This study explores the role and importance of Information and Communication Technology (ICT) volunteer organizations in influencing various dimensions of societal life, namely social, economic, environmental, health, and educational aspects. Through qualitative analysis, this research identifies the significant contributions of ICT volunteer organizations in community empowerment, enhancing digital skills, and providing access to information. The results of the study indicate that the activities of ICT volunteers not only improve digital literacy but also have a broad positive impact on various aspects of life.